Exploring Case Study Method for Library and Information Science Research - Heriyanto, Heriyanto (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2018)
This article explores a case study method for library and information science research. It aims to investigate the implementation of the case study method for Library and Information Science research and seeks to understand how the method has been implemented for the Library and Information Science. Hence some Library and Information research that applied case study method are described and analyzed. The findings show that some phenomenon in the Library and Information Science can be best approached by applying a case study method when the study purposed to address questions like